Immunogenic dynamics and SARS-CoV-2 variant neutralisation of the heterologous ChAdOx1-S/BNT162b2 vaccination: Secondary analysis of the randomised CombiVacS study. (August 2022) - García-Pérez, Javier; González-Pérez, María; Castillo de la Osa, María; Borobia, Alberto M.; Castaño, Luis; Bertrán, María Jesús; Campins, Magdalena; Portolés, Antonio; Lora, David; Bermejo, Mercedes; Conde, Patricia; Hernández-Gutierrez, Lourdes; et al.
Summary: Background: The CombiVacS study was designed to assess immunogenicity and reactogenicity of the heterologous ChAdOx1-S/BNT162b2 combination, and 14-day results showed a strong immune response. The present secondary analysis addresses the evolution of humoral and cellular response up to day 180. Methods: Between April 24 and 30, 2021, 676 adults primed with ChAdOx1-S were enrolled in five hospitals in Spain, and randomised to receive BNT162b2 as second dose (interventional group [IG]) or no vaccine (control group [CG]). Individuals from CG received BNT162b2 as second dose and also on day 28, as planned based on favourable results on day 14. Humoral immunogenicity, measured by immunoassay for SARS-CoV-2 receptor binding domain (RBD), antibody functionality using pseudovirus neutralisation assays for the reference (G614), Alpha, Beta, Delta, and Omicron variants, as well as cellular immune response using interferon-γ and IL-2 immunoassays were assessed at day 28 after BNT162b2 in both groups, at day 90 (planned only in the interventional group) and at day 180 (laboratory data cut-off on Nov 19, 2021). This study was registered with EudraCT (2021-001978-37) and ClinicalTrials.gov (NCT04860739). Findings: In this secondary analysis, 664 individuals (441 from IG and 223 from CG) were included. At day 28 post vaccine, geometric mean titres (GMT) of RBD antibodies were 5616·91 BAU/mL (95% CI 5296·49–5956·71) in the IG and 7298·22 BAU/mL (6739·41–7903·37) in the CG ( p < 0·0001). RBD antibodies titres decreased at day 180 (1142·0 BAU/mL [1048·69–1243·62] and 1836·4 BAU/mL [1621·62–2079·62] in the IG and CG, respectively; p < 0·0001). Neutralising antibodies also waned from day 28 to day 180 in both the IG (1429·01 [1220·37–1673·33] and 198·72 [161·54–244·47], respectively) and the CG (1503·28 [1210·71–1866·54] and 295·57 [209·84–416·33], respectively). The lowest variant-specific response was observed against Omicron-and Beta variants, with low proportion of individuals exhibiting specific neutralising antibody titres (NT50) >1:100 at day 180 (19% and 22%, respectively). Interpretation: Titres of RBD antibodies decay over time, similar to homologous regimes. Our findings suggested that delaying administration of the second dose did not have a detrimental effect after vaccination and may have improved the response obtained. Lower neutralisation was observed against Omicron and Beta variants at day 180. Funding: Funded by Instituto de Salud Carlos III (ISCIII).